Ação in vitro ovicida e larvicida do óleo essencial de Melaleuca alternifolia, livre e nanoestruturado, e terpinen-4-ol sobre o Haemonchus contortus - Grando, Thirssa Helena (2015)
Gastrointestinal parasites are a major sanitary problems faced in the sheep, considerably limiting their profitability, due both to spending on the control measures, well as decrease in their productivity. Among these we can emphasize the helminth Haemonchus contortus, due to their pathogenicity and resistance to existing drugs in the market. With the advancement of parasite resistance, the search for alternative methods and effective anthelmintic products, has been widely studied. In this context, the objective of this study is to evaluate the influence of in vitro administration, the essential oil of Melaleuca (Melaleuca alternifolia) (TTO), a solid lipid nanocarrier made from this oil (nanoTTO), and Terpinen-4-ol (terp-4-ol), major component of the oil on the nematode Haemonchus contortus. To assess the in vitro efficacy of five different concentrations of TTO, and the nanoTTO Terp-4-ol were tested in eggs and infective larvae of H. contortus by means of Larval Hatching Test (LHT), that evaluates the power ovicidal and the Larval Migration Inhibition Test (LMIT), to evaluate the power larvicide of the solutions tested. All groups were tested in sextuplicate in TEL and in quadruplicate in TIML, along with a positive and negative control for the validation of tests. After reading the tests it was observed In LHT, the percentage of inhibition of hatching was 100 % for TTO and terp-4-ol in the concentration of 3.5 mg/mL, with LC50 of 0.43 and 0.63 mg/mL; LC90 of 1.75 mg/mL and 3.12 mg/mL, respectively. NanoTTO obtained less activity, with 82.6 % inhibition at the same concentration. As for LMIT, TTO and nanoTTO had a similar activity with 88.0 % e 84.8 % inhibition, respectively, at a concentration of 56 mg/mL. Terp-4-ol had a greater effect on larvae and, therefore, maintained 85.7 % inhibition at a concentration of 56 mg/mL and 82.4 % at 3.5 mg/mL, demonstrating a high activity in the lower concentration tested. Therefore, the results indicate that all substances that were tested showed ovicidal and larvicidal activity on H. contortus. The terpinen-4-ol being the major component and the results may be presented as one of the components responsible for the anthelmintic action of the oil. TTO, terp-4-ol and nanoTTO may be targets for in vivo studies, besides being a promising line of research in the control and treatment of endoparasitism.